Răspuns :
a)
8a³+12a²+6a+1=8a^3 +(4a^2 +8a^2) +(4a +2a) +1=
(8a^3 +4a^2) +(8a^2 +4a) +(2a +1)=
4a^2 (2a+1) +4a(2a+1) +(2a+1)=
(2a+1)(4a^2 +4a +1)=
(2a+1)(2a+1)^2=
(2a+1)^3
b)
b)a³-3a²b+3ab²-b³=
a^3 -a^2 *b -2a^2 *b +2a*b^2 +a*b^2 -b^3=
(a^3 -a^2 *b) -(2a^2 *b -2a*b^2) +(a*b^2 -b^3)=
a^2 *(a-b) -2ab*(a-b) +b^2 *(a-b)=
(a-b)(a^2 -2ab +b^2)=
(a-b)^3
c)
x³-(2x-y)³=
Aplicam: a^3 -b^3=(a-b)(a^2 +ab +b^2)
x³-(2x-y)³=(x-2x+y)((x^2 +x(2x-y) +y^2)=
(y-x)(3x^2 -xy +y^2)
8a³+12a²+6a+1=8a^3 +(4a^2 +8a^2) +(4a +2a) +1=
(8a^3 +4a^2) +(8a^2 +4a) +(2a +1)=
4a^2 (2a+1) +4a(2a+1) +(2a+1)=
(2a+1)(4a^2 +4a +1)=
(2a+1)(2a+1)^2=
(2a+1)^3
b)
b)a³-3a²b+3ab²-b³=
a^3 -a^2 *b -2a^2 *b +2a*b^2 +a*b^2 -b^3=
(a^3 -a^2 *b) -(2a^2 *b -2a*b^2) +(a*b^2 -b^3)=
a^2 *(a-b) -2ab*(a-b) +b^2 *(a-b)=
(a-b)(a^2 -2ab +b^2)=
(a-b)^3
c)
x³-(2x-y)³=
Aplicam: a^3 -b^3=(a-b)(a^2 +ab +b^2)
x³-(2x-y)³=(x-2x+y)((x^2 +x(2x-y) +y^2)=
(y-x)(3x^2 -xy +y^2)
a) 8a³+12a²+6a+1=8a³+8a²+4a²+4a+2a+1
=8a²(a+1)+4a(a+1)+2a+1
=(a+1)(8a²+4a)+2a+1
=4a(a+1)(2a+1)+2a+1
=(2a+1)(4a(a+1)+1))
b) a³-3a²b+3ab²-b³=(a-b)(a²-2ab+b²)
c) x³-(2x-y)³ aplicam formula pentru a³-b³=(a-b)(a²+ab+b²)
si avem
=(x-2x+y)(x²+x(2x-y)+(2x-y)²)
=(y-x)(x²+2x²-xy+4x²-4xy+y²)
=(y-x)(7x²-5xy+y²)
=8a²(a+1)+4a(a+1)+2a+1
=(a+1)(8a²+4a)+2a+1
=4a(a+1)(2a+1)+2a+1
=(2a+1)(4a(a+1)+1))
b) a³-3a²b+3ab²-b³=(a-b)(a²-2ab+b²)
c) x³-(2x-y)³ aplicam formula pentru a³-b³=(a-b)(a²+ab+b²)
si avem
=(x-2x+y)(x²+x(2x-y)+(2x-y)²)
=(y-x)(x²+2x²-xy+4x²-4xy+y²)
=(y-x)(7x²-5xy+y²)